Should Finland introduce an R&D tax credit? Reflections based on experience with Norwegian R&D policy - Jarle Møen (The Research Institute of the Finnish Economy (ETLA), 2007)
Subsidies to commercial R&D can be given as R&D tax credits or through direct grants. Tax incentives have become an increasingly popular policy tool over the last decades. In this note I discuss the pros and cons of the two forms of subsidies in light of Norway's experience with R&D policy. I review an ongoing evaluation of the Norwegian R&D tax credit introduced in 2002 and reflect on whether it is desirable for Finland to introduce a similar scheme. I suggest that this is not desirable. If Finland introduces an R&D tax credit, I argue that it should be limited to small and medium sized companies.
Keywords: H25; O38; 330; R&D policy; R&D subsidy; R&D tax credit; Finland; Norway; Forschungs- und Technologiepolitik; Steuerbegünstigung; Norwegen